2021
DOI: 10.5539/ijef.v13n9p25
|View full text |Cite
|
Sign up to set email alerts
|

The Short- and Long-Term Effects of Financial Sector Development on Economic Growth in Saudi Arabia: An ARDL Model Analysis

Abstract: The goal of this research was to explore Financial Development and Economic Growth in Saudi Arabia. This would provide evidence pertaining to the relationship between financial sector development and economic growth within the country’s context. In regard to methodology, this study purposed an Autoregressive Distributed Lag (ARDL) model and an ECM model to underline the short and long-term dynamics. To measure financial development, this study implemented the value of credits provided by the financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Numerous researches have confirmed that urban population and economic growth are mutually causal, showing a positive feedback phenomenon of urban growth [2].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researches have confirmed that urban population and economic growth are mutually causal, showing a positive feedback phenomenon of urban growth [2].…”
Section: Introductionmentioning
confidence: 99%